2019
DOI: 10.1017/s1754470x18000260
|View full text |Cite
|
Sign up to set email alerts
|

Working with unaccompanied asylum-seeking young people: cultural considerations and acceptability of a cognitive behavioural group approach

Abstract: This paper outlines a psychological skills group for unaccompanied asylum-seeking young people with a focus on cultural adaptations in the context of a UK mental health service. Unaccompanied asylum-seeking young people have typically experienced multiple losses, traumatic experiences, significant disruption and psychosocial stressors. These experiences occur during a key developmental period and outside of the context of a supportive family environment. Mental health difficulties are estimated to be present i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
37
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(40 citation statements)
references
References 69 publications
0
37
1
1
Order By: Relevance
“…Other interventions and support were implemented alongside NET; therefore, the outcomes shown may not be only attributable to NET. However, evaluation of other psychosocial interventions within this client group did not demonstrate the same improvement in PTSD symptoms (King & Said, 2019).…”
Section: Discussionmentioning
confidence: 86%
See 2 more Smart Citations
“…Other interventions and support were implemented alongside NET; therefore, the outcomes shown may not be only attributable to NET. However, evaluation of other psychosocial interventions within this client group did not demonstrate the same improvement in PTSD symptoms (King & Said, 2019).…”
Section: Discussionmentioning
confidence: 86%
“…It has been demonstrated that UAM may be better able to communicate mental health needs once they are already in contact with mental health services (Sanchez-Cao, Kramer, & Hodes, 2013). King and Said (2019) found that offering a psychological skills group enabled young people to develop their relationship to help and supported young people to engage in trauma-focused therapy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, immigrants and refugees are less inclined than their native‐born counterparts to seek or be referred to mental health agencies (Le Meyer, Zane, Cho, & Takeuchi, 2009). In line with this, research has begun to highlight that group approaches with unaccompanied young people allow for the experience of peer support and the normalisation of therapeutic input (King & Said, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Working with unaccompanied asylum-seeking young people: cultural considerations and acceptability of a cognitive behavioural group approach (King and Said, 2019) This paper describes the development of a culturally adapted intervention and outlines a psychological skills group for unaccompanied asylum-seeking children (UASC). The authors also report feasibility, acceptability and preliminary effectiveness of the intervention.…”
Section: Summary and Discussionmentioning
confidence: 99%